2017
DOI: 10.4236/jcdsa.2017.73023
|View full text |Cite
|
Sign up to set email alerts
|

Ageing-Related Features of Hair and Scalp in Chinese Women by Clinical Evaluation Study

Abstract: There are previous studies of ageing hair and scalp in Caucasians and some Asians, such as Koreans and Japanese. However, the characteristics of scalp and hair have not yet been studied in Chinese, the largest population in the world, especially in terms of ageing. The purpose of this study is to investigate ageing features in Chinese women's hair and scalp. Methods: In total, 1343 women in China aged 20 to 65 participated in this research. Hair density and diameter were measured and analysed with Folliscope®.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
0
0
1
Order By: Relevance
“…9 A study conducted on Chinese women showed that the reduction in hair diameter reached its peak in the 40s age range. 17 In our study, the highest reduction in hair diameter was found among individuals older than 50 years. However, a full comparison cannot be made, as the Chinese study was conducted on females only.…”
Section: Discussionsupporting
confidence: 42%
“…9 A study conducted on Chinese women showed that the reduction in hair diameter reached its peak in the 40s age range. 17 In our study, the highest reduction in hair diameter was found among individuals older than 50 years. However, a full comparison cannot be made, as the Chinese study was conducted on females only.…”
Section: Discussionsupporting
confidence: 42%
“…Alterações da estrutura vascular, inflamação e vasodilatação são clinicamente manifestados como eritema, uma vez que ocorre aumento anormal da hemoglobina na derme papilar (Xu et al, 2016). O eritema, por sua vez, está fortemente associado ao envelhecimento da pele do rosto e do couro cabeludo, surgindo por volta dos 20 anos de idade e intensificando-se a partir de 40 anos (Kim et al, 2017). Além disso, eritema e telangiectasia são relevantes manifestações de fotoenvelhecimento (El Kahky; Diab; Ali, 2018).…”
Section: Vasos Sanguíneosunclassified